2004
DOI: 10.1097/01.rhu.0000129082.42094.fc
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Ischemic Heart Disease in Gout

Abstract: In this work, metabolic syndrome was very common among patients with gout. Sixteen percent of the patients, although previously asymptomatic, had IHD, they all had metabolic syndrome. Gouty patients frequently first seek medical care from a rheumatologist. The rheumatologist can have an important role in detecting metabolic syndrome and risk factors for cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
17

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 20 publications
1
22
1
17
Order By: Relevance
“…In fact, the prevalence is substantially higher than among those who experienced myocardial infarction or stroke (41-44%) in the same NHANES study (18). These data expand on previous studies that demonstrated a close relationship between hyperuricemia and insulin resistance syndrome (6,9,10), and on the recent case series of gout and metabolic syndrome (12,13), thereby supporting a pathogenetic overlap between these conditions. Higher insulin levels are known to reduce renal excretion of urate (11,19 -21).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In fact, the prevalence is substantially higher than among those who experienced myocardial infarction or stroke (41-44%) in the same NHANES study (18). These data expand on previous studies that demonstrated a close relationship between hyperuricemia and insulin resistance syndrome (6,9,10), and on the recent case series of gout and metabolic syndrome (12,13), thereby supporting a pathogenetic overlap between these conditions. Higher insulin levels are known to reduce renal excretion of urate (11,19 -21).…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, the reduced renal excretion of urate among patients with metabolic syndrome may explain the increased frequency of hyperuricemia. Furthermore, recent case series reported that the prevalence of metabolic syndrome was high among patients with gout (82% in Mexican men [12] and 44% in Korean men [13] compared with 5% in the Korean general population [14]). Although these hospital-based case series (12,13) may have included patients who are sicker than individuals from the general population, the totality of available information points toward a strong link between gout and metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8,[16][17][18][19][20]. Однако частота выяв-ления отдельных заболеваний в разных группах больных по-дагрой может существенно различаться.…”
Section: Discussionunclassified
“…Кроме того, на течение подагры могут влиять наличие коморбидных, или сочетанных, заболеваний (СЗ) и мета-болических нарушений, частота которых у больных пода-грой крайне высока [9,10]. Однако как влияют снижение массы тела или артериального давления, улучшение пока-зателей липидного обмена на уровень МК в крови и ча-стоту приступов артрита у больных подагрой, неизвестно.…”
Section: контактная информацияunclassified